Investigation on physical activation of some Mongolian coals - Damdin, Batkhishig; Purevsuren, Barnasan; Zhang, Yuanli; Sun, Haizhen; Alyeksandr, Ariunaa; Ariunbold, Ankhtuya; Munkhtaivan, Battsetseg; Jargalsaikhan, Namkhainorov; Sanjaa, Batbileg (Mongolian Journal of Chemistry, 2019)
Activation characteristics of four different Mongolian coals were investigated. The coals were carbonized at temperatures of 550 °C and the obtained samples were activated by preheated steam. The pore size, pore volume and surface areas of all activated carbons (AC) have been determined by adsorption of nitrogen (N2) gas. The BET surface areas of Aduunchuluun (ACAC), Shivee Ovoo (SCAC), Baganuur (BCAC) coal and Ulaan Ovoo coals (UCAC) are 283, 205, 251 and 460 m2/g respectively. Langmuir surface area is 283 m2/g of ACAC, 230 m2/g of SCAC, 537 m2/g in UCAC and 254 m2/g in BCAC.